2020
DOI: 10.1142/s0218625x19502147
|View full text |Cite
|
Sign up to set email alerts
|

ION BEAM IRRADIATION EFFECTS ON SURFACE MORPHOLOGY AND OPTICAL PROPERTIES OF ZnO/PVA COMPOSITES

Abstract: Polymer nanocomposites composed of zinc oxide nanoparticles (ZnO NPs)-doped polyvinyl alcohol (PVA) polymer matrix have been synthesized using solvent casting preparation method. The ZnO/PVA polymer nanocomposite films are irradiated with different argon ion beam fluences using broad-beam ion source. The prepared films are characterized using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and UV–visible spectroscopy. The XRD shows that ZnO NPs are su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…Another indicator for the shifting of the absorption edge was the structural modifications in MC matrix, which has been determined by the XRD results and the molecular interactions of MC polymer chains and the AgNPs. Specifically, the shift in the optical absorption edge reflects the electronic conjugation between the AgNPs and the PANI beside the increase in the degree of disorder for those composite films [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Another indicator for the shifting of the absorption edge was the structural modifications in MC matrix, which has been determined by the XRD results and the molecular interactions of MC polymer chains and the AgNPs. Specifically, the shift in the optical absorption edge reflects the electronic conjugation between the AgNPs and the PANI beside the increase in the degree of disorder for those composite films [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…This indicates a good miscibility between Cu and PET chains and supports XRD pattern and AFM images. It is concluded that the amount of optical transmission depends on the defect state and the reduction in the disorder structure [33] due to the deposited CuNPs. The CuNPs exhibited transmittance band around 580 nm, related to conduction electrons excitation of the Cu metal NPs after their unique interaction with the electromagnetic light eld.…”
Section: Resultsmentioning
confidence: 99%
“…Such hydrogen bonding has led to a considerable widening of hydroxyl peak especially for the sample containing 6% nanoparticle 51 . The band at 1113 cm −1 is related to the CO stretching vibration of acetyl group present on the PVA backbone, whose intensity is slightly decreased for the ZnO/PVA due to the presence of ZnO NPs 47 . The hydroxyl groups of PVA have a very strong tendency to form charge transfer complex with ZnO nanoparticles through chelation 39 …”
Section: Resultsmentioning
confidence: 99%